Inactivation kinetics of selected pathogenic and non-pathogenic bacteria by aqueous ozone to validate minimum usage in purified water - Lou, Yuqian; Kasler, David R.; Hawkins, Zach L.; Li, Zhen; Sannito, Dan; Fritz, Ronald D.; Yousef, Ahmed E. (Frontiers in Microbiology, 2024)
Ozone is often used as an antimicrobial agent at the final step in purified water processing. When used in purified bottled water manufacturing, residual ozone should not exceed 0.4 mg/L, per US-FDA regulations. These regulations require the control of Escherichia coli and other coliform bacteria; however, non-coliform pathogens can contaminate bottled water. Hence, it is prudent to test the efficacy of ozone against such pathogens to determine if the regulated ozone level adequately ensures the safety of the product. Inactivation of selected pathogenic and nonpathogenic bacteria in purified water was investigated as a function of ozone dose, expressed in Ct units (mg O3*min/L). Bacterial species tested were Enterococcus faecium, E. coli (two serotypes), Listeria monocytogenes (three strains), Pseudomonas aeruginosa, and Salmonella enterica (three serovars). Resulting dose (Ct)-response (reduction in populations' log10 CFU/mL) relationships were mostly linear with obvious heteroscedasticity. This heteroscedastic relationship required developing a novel statistical approach to analyze these data so that the lower bound of the dose-response relationships can be determined and appropriate predictive models for such a bound can be formulated. An example of this analysis was determining the 95%-confidence lower bound equation for the pooled dose-responses of all tested species; the model can be presented as follows: 𝐿𝑜𝑔 𝑝𝑜𝑝𝑢𝑙𝑎𝑡𝑖𝑜𝑛 𝑟𝑒𝑑𝑢𝑐𝑡𝑖𝑜𝑛 = 3.80 𝐶𝑡 + 1.84. Based on this relationship, application ozone at a Ct of 0.832 and 21°C achieves ≥ 5-log reduction in the population of any of the tested pathogens. This dose can be implemented by applying ozone at 0.832 mg/L for 1 min, 0.416 mg/L for 2 min, or other combinations. The study also proved the suitability of E. faecium ATCC 8459 as a surrogate strain for the pathogens tested in the current study for validating water decontamination processes by ozone. In conclusion, the study findings can be usefully implemented in processing validation of purified water and possibly other water types.